Peningkatan Kesadaran Keamanan Dan Risiko Penggunaan E-Wallet Sebagai Alat Pembayaran Digital Pada Siswa SMA TRIGUNA 1956 Jakarta - Chika Maulidia Asrofah; Gracya Silaban; Reizan Ahmad Rifky; Yeni Septiani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. The development of information and communication technology in the modern era has experienced rapid progress. This has had a significant impact on daily life, particularly regarding online payment and shopping transactions. The use of digital wallets (e-wallets) in Indonesia has become increasingly widespread in recent years. Despite the convenience offered, various security risks also lurk. This Community Service (PKM) activity aims to increase the understanding, awareness, and skills of Triguna 1956 High School students in utilizing digital financial services wisely, safely, and responsibly. The activity's implementation methods included outreach, interactive training, discussions, and evaluation of participants' understanding. The results of the activity indicated an increase in participants' knowledge regarding the level of security and risks in e-wallet use, as well as their ability to implement safe financial management practices in the digital era. This activity is expected to support a sustainable increase in awareness of security and risks in use, especially in secondary education settings. Keywords: Security, Risk, E-wallet, Community Service.